Research Program: Modeling of Young Gymnasts' Training Process - O. M. Khudolii (OVS LLC, 2019)
The study purpose was to substantiate theoretical and methodological grounds and the concept of a research program of the training process based on modeling of individual components of the young gymnasts' training system.  Materials and methods. The study involved: 30 gymnasts - 3rd senior category, 30 gymnasts - 2nd senior category, 26 gymnasts - 1st senior category. Young gymnasts participating in the experiment received athletic titles from the 1st category to master of sports (1st c. - 18 persons, CMS - 15 persons, MS - 12), won competitions of different levels. To substantiate the research program, the study used the following methods: modeling, systems approach, methods of theoretical analysis and generalization to reveal the essence, leading development trends of the young gymnasts' training system and to define theoretical prerequisites and methodological approaches to its further improvement; pedagogical testing, methods of recording sensorimotor reactions, methods of recording the cardiovascular system state, observation and pedagogical experiment to determine young gymnasts' model characteristics, modes of training loads; methods of mathematical analysis (logistic and asymptotic functions) to determine the regularities of allocating the means of primary focus during motor abilities development, teaching gymnastic exercises and training for competitions; mathematical methods of planning multifactorial experiments to study the regularities of motor abilities development, teaching process and training for competitions. The obtained experimental material was processed using statistical analysis software (SPSS 20). Results. The developed conceptual approaches to determining the normative characteristics of training loads in the process of young gymnasts' training include: analysis of the effects of different modes of training on a change in the functional state; determination of the optimal increase in the functional state indicators; calculation of a mode of training that can ensure the optimal increase in the indicators of young gymnasts' functional state. Conclusions. The developed research program makes it possible to define the regularities of motor abilities development, teaching gymnastic exercises and training for competitions; to obtain the models of young gymnasts' training process. As a result of implementing the research program, the study substantiated factorial designs for studying the influence of modes of alternation of exercises and rest on the effectiveness of motor abilities development, motor skills formation, and the effectiveness of training young gymnasts for competitions.